EV products obtained from iPSC-derived MSCs show batch-to-batch variations in their ability to modulate allogeneic immune responses in vitro - Tertel, Tobias; Dittrich, Robin; Arsène, Pierre; Jensen, Arne; Giebel, Bernd (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stromal cells (MSCs) have demonstrated therapeutic potential in diverse clinical settings, largely due to their ability to produce extracellular vesicles (EVs).These EVs play a pivotal role in modulating immune responses, transforming proinflammatory cues into regulatory signals that foster a pro-regenerative milieu. Our previous studies identified the variability in the immunomodulatory effects of EVs sourced from primary human bone marrow MSCs as a consistent challenge. Given the limited proliferation of primary MSCs, protocols were advanced to derive MSCs from GMP-compliant induced pluripotent stem cells (iPSCs), producing iPSC-derived MSCs (iMSCs) that satisfied rigorous MSC criteria and exhibited enhanced expansion potential. Intriguingly, even though obtained iMSCs contained the potential to release immunomodulatory active EVs, the iMSC-EV products displayed batch-to-batch functional inconsistencies, mirroring those from bone marrow counterparts. We also discerned variances in EV-specific protein profiles among independent iMSC-EV preparations. Our results underscore that while iMSCs present an expansive growth advantage, they do not overcome the persistent challenge of functional variability of resulting MSC-EV products. Once more, our findings accentuate the crucial need for batch-to-batch functional testing, ensuring discrimination of effective and ineffective MSC-EV products for considered downstream applications.